Strategi Kampanye Daur Ulang Sampah Plastik untuk Meningkatkan Kepedulian Masyarakat melalui Konten Instagram @Ecollabo8 - Ni Made Yunita; Tira Fitriawardhani; Julyanto Ekantoro (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Plastic waste is a global issue that threatens the environment due to its non-biodegradable nature. This study aims to examine the campaign strategies conducted by the Instagram account @Ecollabo8 in increasing public awareness regarding plastic waste recycling. The method used is descriptive qualitative, with data collection techniques including documentation, non-participant observation, and literature studies of @Ecollabo8's content from September 2023 to September 2025. The results show that @Ecollabo8 implements a comprehensive campaign strategy through four social media pillars: Communication, Collaboration, Education, and Entertainment. This strategy proved effective in increasing public concern, as reflected in Cognitive, Affective, and Conative responses in digital interactions.